ORGANOLEPTICAL TEST OF BAKPAO PRODUCTION WITH MIXTURE PURPLE SWEET POTATO FLOUR AND WHEAT FLOUR (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2022)
Purple sweet potato is a functional food that has an energy content of 123 calories and 0.94 grams of fat per 100 grams of material. In addition, purple sweet potato contains Beta-carotene which functions as a controller of the hormone melatonin, which has a role in the formation of endocrine hormones. Our research has a target to analyze the effect of a mixture of wheat flour and purple sweet potato flour on the organoleptic test of purple sweet potato buns. Our research was conducted at the Chemistry Laboratory of the Faculty of Agriculture, Muhammadiyah University of Palembang. This research used a randomized block design (RBD) arranged in a non-factorial manner with a comparative treatment aspect between purple sweet potato flour and wheat flour which consisted of five treatment components and was repeated three times. The parameters observed in this study were organoleptic tests including color, taste and aroma. Results of the study Organoleptic test results had a significant effect on the color, aroma and taste of the purple sweet potato buns produced. The highest values for color, aroma and taste were found in the T3 treatment (50% purple sweet potato flour and 50% wheat flour) with an average value of 4.25; 4.25 and 4.15